2021
DOI: 10.14719/pst.2021.8.1.984
|View full text |Cite
|
Sign up to set email alerts
|

Yield and morpho physical characters of some modern aus rice varieties at Khagrachari

Abstract: Aus, aman and boro are three rice cultivating seasons in Bangladesh. Among these aus is the least cultivated and grown in comparatively small scale due to prevailing drought and less availability of surface water for irrigation. Modern varieties of aus rice cover a significant area of the country conversely local cultivars cover a small area. Aus rice requires much fewer inputs than aman and boro. Due to continuous declination of groundwater level, nowadays more emphasis is given on the extension of aus cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies reported that BINAdhan-19 is a standard short-duration Aus variety with a semi-dwarf phenotype [35,36]. In this study, the check variety BINAdhan-19 had the lowest DM, followed by the accessions BU-R-ACC-02, BU-R-ACC-05, R3-49-2-1-1, R2-36-3-1-1, BU-R-ACC-01, BU-R-ACC-03, BU-R-ACC-04, BU-R-ACC-08 and R1-29-6-1-1, when compared with other investigated rice accessions (Figure 2 and Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that BINAdhan-19 is a standard short-duration Aus variety with a semi-dwarf phenotype [35,36]. In this study, the check variety BINAdhan-19 had the lowest DM, followed by the accessions BU-R-ACC-02, BU-R-ACC-05, R3-49-2-1-1, R2-36-3-1-1, BU-R-ACC-01, BU-R-ACC-03, BU-R-ACC-04, BU-R-ACC-08 and R1-29-6-1-1, when compared with other investigated rice accessions (Figure 2 and Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Khairul Islam et al 2021). BRRI dhan65 variety showed the lowest yield as compared to Binadhan-14, Binadhan-19, BRRIdhan43, BRRI dhan48, BRRI dhan55 and BRRI dhan65 varieties(Chowhan et al 2021). PEG-applied (5%, w/v) 38-day-old Binadhan-11, BRRI dhan 52, Binadhan-7, BRRI dhan 71 plants during 17 days were analysed in terms of root morphology.…”
mentioning
confidence: 84%